2012
DOI: 10.17955/tvr.112.3.m.701
|View full text |Cite
|
Sign up to set email alerts
|

The Value of a Learning Community to Support Telepractice for Infants and Toddlers with Hearing Loss

Abstract: It has been almost 10 years since I was indoctrinated into the specialized field of telepractice. My introduction was based on a persistent need. At the time, as the director of a statewide early intervention program, I was committed to delivering the same high-quality early intervention services using the communication approach selected by each family to all children in the state irrespective of the geographic location in which the children lived. This presented a challenge as many rural communities did not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…Unfortunately, few rigorous studies of the efficacy or cost-effectiveness of services provided through two-way conferencing systems have been conducted ( Hjelm, 2005 ; Mashima & Doarn, 2008 ; Scott et al, 2007 ; Wootton, 2001 ). A recent monograph provides the most current published information about the use of TI to support early intervention to infants and toddlers who are DHH ( Blaiser, Edwards, Behl, & Muñoz, 2012 ; Behl, Houston, & Stredler-Brown, 2012 ). Similar to previous literature on this topic, articles in the monograph describe applications of this technology and draw attention to the need for better evidence, with very little evidence being reported.…”
mentioning
confidence: 99%
“…Unfortunately, few rigorous studies of the efficacy or cost-effectiveness of services provided through two-way conferencing systems have been conducted ( Hjelm, 2005 ; Mashima & Doarn, 2008 ; Scott et al, 2007 ; Wootton, 2001 ). A recent monograph provides the most current published information about the use of TI to support early intervention to infants and toddlers who are DHH ( Blaiser, Edwards, Behl, & Muñoz, 2012 ; Behl, Houston, & Stredler-Brown, 2012 ). Similar to previous literature on this topic, articles in the monograph describe applications of this technology and draw attention to the need for better evidence, with very little evidence being reported.…”
mentioning
confidence: 99%
“…Part C of the Individuals with Disabilities Education Act (IDEA) ensures that children who have, or are at-risk for, developmental delays receive early intervention services. Unfortunately, many children with special needs, including those who are Deaf/Hard-of-Hearing (DHH), are unable to access specialized early intervention services because of their proximity to services, the inadequate number of specialized early intervention professionals, and other constraints pertaining to daily routines and financial limits (Behl, Houston, & Stredler-Brown, 2012). Yet, with this increase in need, there has been a noted shortage of early intervention providers with expertise in serving children who are DHH, particularly in rural and remote areas (Muñoz, Bradham, & Nelson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As increasing evidence to support telepractice grows, so has the adoption of telepractice by early intervention programs throughout the United States. For example, in 2010, there were approximately five early intervention programs using telepractice or in the planning stages for adoption of this service delivery model (Behl et al, 2012). In the last 6 years, the number of early intervention programs, particularly those serving families of infants and toddlers who are DHH, has increased dramatically, with an increase in the National Hearing Assessment and Management (NCHAM) Telepractice Learning Community membership from 12 in 2010 to 46 in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Although traditionally used to provide healthcare services at a distance, research has shown that eHealth can have a broader application to EI for families and professionals. From a patient and family perspective, eHealth can provide earlier access to intervention services by: enabling virtual home visits (Hayes, Boada, & Coe, 2015;Olsen, Fiechtl, & Rule, 2012;Stredler-Brown & Alverson, 2012); providing opportunities for engaging siblings, grandparents, and local professionals through videoconferencing (McCarthy, Muñoz, & White, 2010); and improving family outcomes, confidence, and satisfaction (Behl, Houston, & Stredler-Brown, 2012;Chi & Demiris, 2015;Davis, Hopkins, & Abrahams, 2012). From a professional perspective, eHealth can improve professionals' effectiveness and adherence to clinical guidelines .…”
Section: Introductionmentioning
confidence: 99%
“…As early hearing intervention programs need to address professionals' training needs Houston, Muñoz, & Bradham, 2011), eHealth can also facilitate professional development by providing opportunities to connect with specialists, participate in online courses, collaboration, and networking between specialists and local professionals (Moffatt & Eley, 2010). Recent studies have suggested that eHealth can provide more opportunities to meet educational needs of hearing professionals in the case of shortage of well-trained professionals in hearing services (Behl et al, 2012;Hayes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%